Ethics in biomedical research international perspectives - Häyry, Matti; Takala, Tuija, 1971-; Herissone-Kelly, Peter (Value Inquiry Book Series, 2007)
This book deals with the international assessment and regulation of biomedical research. In its chapters, some of the leading figures in today’s bioethics address questions centred on global development, scientific advances, and vulnerability. The series Values In Bioethics makes available original philosophical books in all areas of bioethics, including medical and nursing ethics, health care ethics, research ethics, environmental ethics, and global bioethics.